Conscience: what is its history and does it have a future?. Issue 3 (3rd April 2019) - Cottingham, John
ABSTRACT: This chapter looks briefly at the religious roots of the notion of 'conscience' in the Judaeo-Christian tradition, before examining the rise in the early-modern period of a 'naturalizing' approach that tries to explain our moral capacities in purely empirical terms, by reference to our natural inclinations and drives. The problem with this approach, highlighted by Joseph Butler, is that it fails to account for the authority or 'normativity' of the deliverances of conscience. An examination of the naturalistic approaches of J.S. Mill, Charles Darwin and Sigmund Freud shows that none of them manages to escape the difficulty. It is suggested in conclusion that only a traditional theistic framework may be adequate for doing justice to the role of conscience in our lives.